An Introduction To The Baba Creole Malay Of Melaka - Carol, Ong (Universiti Sains Malaysia, 1985)
In the following chanters, the Baba Creole Malay Language of the Babas of Melaka will be studied under three areas. The first is its nature and origin as a creole language, that is its historical background and its general characteristics.